Pingwei Powder alleviates high-fat diet-induced colonic inflammation by modulating microbial metabolites SCFAs - Liu, Tangjuan; Ou, Guosen; Wu, Jialin; Wang, Shiqi; Wang, Hao; Wu, Ziqi; Jiang, Yawen; Chen, Yaokang; Xu, Huachong; Deng, Li; Chen, Xiaoyin; Xu, Lu (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPingwei Powder (PWP), a renowned traditional Chinese medicine (TCM) formula, it has demonstrated excellent therapeutic effects in ulcerative colitis (UC), yet its underlying pharmacological mechanisms remain unclear. This study aims to investigate the therapeutic effect of PWP on the aggravation of colonic inflammation induced by a high-fat diet and particularly focuses on its regulatory mechanisms on gut microbiota, which are closely related to UC.MethodsNetwork pharmacology analysis was employed to screen potential pharmacological targets of PWP for UC. Histological changes in colonic tissue were observed using hematoxylin and eosin (H&E) staining, and immunofluorescence staining was performed to evaluate the expression of tight junction proteins (ZO1 and Occludin). Western blotting was used to detect the expression levels of proteins related to the PI3K/AKT/mTOR pathway, ZO1, and Occludin. qRT-PCR was conducted to measure the relative expression of inflammatory cytokines (IL-1β, IL-17, IL-6, and TNF-α) in colonic tissue. Additionally, 16S rDNA sequencing was performed to analyze gut microbiota alterations, and GC/MS was used to quantify short-chain fatty acids (SCFAs) in gut contents. The gutMgene database was utilized to validate the mediating roles of gut microbiota metabolites in the pharmacological effects of PWP. And their mediating role in PWP efficacy was verified by fecal microbiota transplantation (FMT) and butyrate supplementation.ResultsNetwork pharmacology analysis predicted that PWP may regulate the PI3K/AKT pathway to exert therapeutic effects in UC. Experimental validation showed that PWP significantly downregulated the levels of PI3K, pAKT/AKT, and pmTOR/mTOR in colonic tissue, thereby enhancing autophagy in colonic epithelial cells, as evidenced by decreased levels of P62 and increased LC3B-II/LC3B-I ratios. Furthermore, 16S rDNA sequencing combined with targeted SCFAs analysis of gut contents revealed that the pharmacological effects of PWP may be mediated by increasing the abundance of SCFAs-producing gut microbiota (Alistipes and Parabacteroides) and elevating the levels of SCFAs in the gut.ConclusionPWP enhances the abundance of SCFAs-producing bacteria (Alistipes and Parabacteroides) in the gut, increases the levels of butyrate, and inhibits the PI3K/AKT/mTOR pathway in the colon. These effects promote colonic autophagy and contribute to the resolution of colonic inflammation.